Structuring best value delivery process of PPP infrastructure projects in Malaysia - Pathrose Gomez, Christy (2013)

(untitled)
The rapid human population growth rate coupled with the need for improved delivery in infrastructure projects has necessitated the need for the private sector participation in the delivery of much needed infrastructure facilities and services. Public Private Partnerships (PPP) is one of such private sector driven procurement approach which has evolved to solve the infrastructure deficits, and Malaysia is not left out in the adoption of this innovative procurement approach. However, its practice is bedevilled with issues related to the ineffective structuring of the private sector body that is responsible for delivering the infrastructure project through the public private partnership approach. This paper is the result of a preliminary study undertaken as part of a funded research to establish operational strategy indicators (performance measures) to be matched with relevant VfM outcomes using a Balanced Scorecard (BSC) approach linking cause to effect. Initial results indicate a tendency towards high business strategy rather than service. Data was collected from a series of semi structured interviews that were conducted with PPP practitioners. Additionally, using critical approach, based on document analysis it is clear that current policy and practice with regard to the structuring the Special Purpose Vehicle (SPV), aimed at achieving Value for Money (VfM) objectives are lacking. The findings of the research indicates that prioritised VfM strategies according to pre-construction, construction and post-construction phases based on using the BSC as a management system together with comprehensive policies that can serve towards structuring a more effective SPV project organization can enhance the delivery of PPP infrastructure projects in Malaysia.